Persepsi Guru terhadap Peran Kepemimpinan Kepala Sekolah - Yunita Aisyah; Inom Nasution; Budi Budi (STIKes Ibnu Sina Ajibarang, 2024)
The purpose of this research is to find out how big the role of teacher perceptions regarding school principal leadership is. The research that has been carried out by researchers is entitled;